A Spatiotemporal Analysis of Humidity Pattern in Bali using Space-Time Kriging with Seasonal Drift - Nugroho, Salma Fitri; Fitriani, Rahma; Iriany, Atiek (JTAM (Jurnal Teori dan Aplikasi Matematika), 2025)
Climate plays a vital role in framing the characteristics of tourist activity. Humidity reflects the amount of moisture in the air relative to the maximum it can hold at a specific temperature, it has a direct influences on perceived comfort levels. Bali, one of the most popular destinations renowned for its breathtaking natural beauty and varied landscapes. However, this island is currently served by only four climate observation stations which are insufficient to capture the humidity across the island. Therefore, this research aims to model humidity levels in Bali based on four observed locations at 2019-2023 using the space-time kriging with seasonal drift and predict humidity at unobserved locations. This approach was choosen due to the strong seasonal pattern exhibited in climate data, which leading to non-stationary. The space-time kriging method is applied to the residuals. The most effective model identified was the exponential-exponential-Gaussian (Exp-Exp-Gau) model using a sum-metric structure. This model provided the lowest RMSE of 2.1442. Humidity contour maps suggest a gradual decline in humidity levels over time across Bali. This trend may have significant impacts for both environmental quality and the tourism sector. Lower humidity levels could lead to increased discomfort for tourists and potentially reduce the attractiveness of the destination. Theoretically, the development of the kriging model enhances the accuracy of predictions, as shows by the low RMSE. Practically, these findings emphasize the importance of integrating climate considerations into sustainable tourism planning and management strategies based on the humidity information.